Rational Design and General Synthesis of Multimetallic Metal–Organic Framework Nano‐Octahedra for Enhanced Li–S Battery. Issue 45 (23rd September 2021) - Li, Wenting; Guo, Xiaotian; Geng, Pengbiao; Du, Meng; Jing, Qingling; Chen, Xudong; Zhang, Guangxun; Li, Hongpeng; Xu, Qiang; Braunstein, Pierre; Pang, Huan
Abstract: Metal–organic frameworks (MOFs), which consist of central metal nodes and organic linkers, constitute a fast growing class of crystalline porous materials with excellent application potential. Herein, a series of Mn‐based multimetallic MOF (bimetallic and trimetallic MIL‐100) nano‐octahedra are prepared by a facile one‐pot synthetic strategy. The types and proportions of the incorporated elements can be tuned while retaining the original topological structure. The introduction of other metal ions is verified at the atomic level by combining X‐ray absorption fine structure experiments and theoretical calculations. Furthermore, these multimetallic Mn‐based MIL‐100 nano‐octahedra are utilized as sulfur hosts to prepare cathodes for Li–S batteries. The MnNi‐MIL‐100@S cathode exhibits the best Li–S battery performance among all reported MIL‐100@S composite cathode materials, with a reversible capacity of ≈708.8 mAh g −1 after 200 cycles. The synthetic strategy described herein is utilized to incorporate metal ions into the MOF architecture, of which the parent monometallic MOF nano‐octahedra cannot be prepared directly, thus rationally generating novel multimetallic MOFs. Importantly, the strategy also allows for the general synthesis and study of various micro‐/nanoscale MOFs in the energy storage field. Abstract : A series of Mn‐based multimetallic metal–organic framework (MOF) nano‐octahedra are prepared. The synthetic strategy is utilized to incorporate metal ions into the MOF architecture, of which the parent monometallic MOF nano‐octahedra could not be prepared directly, thus rationally generating novel multimetallic MOFs, which also allows for the general synthesis of various micro‐/nanoscale MOFs in the energy storage field.